Penerapan Algoritma Slope One dalam Collaborative Filtering Sebagai Sistem Rekomendasi Tempat Kost di Denpasar - Andari, Ni Wayan Anti; Supriana, I Wayan; Suputra, I Putu Gede Hendra; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 1 (2024): JELIKU Volume 13 No 1, August 2024DO - 10.24843/JLK.2024.v13.i01.p01, 2024)
The city of Denpasar serves as the administrative, business, educational, and tourism center in Bali, attracting numerous visitors including students and workers from outside the region. This has led to high demand for temporary accommodation, commonly known as boarding houses or "kost". The appropriate solution to address this issue is by developing a boarding house recommendation system to assist prospective renters in finding a place that suits their needs and preferences. This system is built using two algorithms: collaborative filtering and Slope One, to generate accurate and relevant recommendations. In the evaluation phase, usability testing is conducted using the SUS method. The results of usability testing in terms of Acceptability, Grade Scale, and Adjective Rating obtained an average score of 82.03. Accuracy testing is done using Mean Absolute Error (MAE), which resulted in an accuracy with the highest value being 0.06. A higher accuracy indicates better recommendations. The ultimate goal is to help users, especially students, efficiently find suitable boarding houses in Denpasar through information technology. Keywords : Boarding houses, Recommendation System, Collaborative Filtering, Usability Testing, Mean Absolute Error (MAE)